Multifunctional Rural Regional Development: Evidence from the John Day Watershed in Oregon. (March 2015) - Hibbard, Michael; Senkyr, Lauren; Webb, Mark
A new approach to rural regional development planning seems to be emerging. Substantively, it combines socioeconomic development with a conservation and restoration approach to environmental planning and natural resource management. With respect to process, it moves from more rational–comprehensive, top–down approaches toward decentralized, bottom–up strategies. This paper reports a key case from the American West. We begin by reviewing the evolution and current state of rural regional development planning. Next we describe the case study area, the planning situation, and our research methods. Then we report landowners' and resource managers' perceptions of the emerging approach and their implications.